Implementasi BUMDes sebagai Instrumen Pemberdayaan Masyarakat Desa: Studi Empiris di Desa Balongpanggang Kecamatan Balongpanggang Kabupaten Gresik - Jessica Wildani Habibah; Tukiman Tukiman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the Implementation of Village-Owned Enterprises (BUMDes) as an Instrument for Village Community Empowerment: An Empirical Study in Balongpanggang Village, Balongpanggang District, Gresik Regency. The southern area of Gresik still experiences development disparities that have resulted in suboptimal BUMDes management. However, BUMDes Jaya Abadi in Balongpanggang Village has shown relatively positive development and has received several awards, making it an interesting case for further analysis. This research employs a qualitative approach using data collection techniques such as observation, in-depth interviews, and documentation. The findings indicate that the implementation of BUMDes Jaya Abadi has been carried out through the management of various village business units and the application of four development aspects as the basis of its activities. Nevertheless, the role of BUMDes in encouraging active community participation and strengthening local capacity has not been fully optimized. The main challenges include limited human resources, low public understanding of BUMDes programs, and the underutilization of digital technology in business governance. Therefore, strengthening communication, improving managerial capacity, implementing digital systems, and expanding community participation are necessary to achieve more effective and sustainable BUMDes implementation.